Леди-мафия: [роман] / Владимир Колычев - Колычев Владимир Григорьевич (ЭКСМО-Пресс, 2001)
Экземпляры: п/ф (ретроконверсия) / Инвентарный номер: 37946 / Цена: 34.80 / Сис.шифр: Р2 / Авт.знак: К 60 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6